PENINGKATAN HASIL PADA TIGA VARIETAS KACANG TANAH (Arachis hipogeae L.) DENGAN PENGGUNAAN PUPUK ORGANIK - Eny Hari Widowati; Bistok Hasiholan; Alfina Handayani (JURNAL LITBANG PROVINSI JAWA TENGAH, 2012)
The objective of the research was 1).Agrotechnology adaptation test of some peanut varietes, there were Kancil, Jepara and Cidaun strain in use of organic fertilizers, 2). Aspergillus flavus test on research land site and 3).analyze farm production. The research location in Suwawal Timur village, Pakis Aji, Jepara in April to September 2011. Research using Randomized Block Design (RBD) with 9 treatments and 3 replications. The treatments were attempted: Treatment A = Cidaun strain + 1 ton organic fertilizer per ha, B = Cidaun strain + 1.5 ton organic fertilizer per ha, C = Cidaun strain+2 ton organic fertilizer per ha, D = Jepara variety + 1 ton organic fertilizer per ha, E = Jepara variety + 2 ton kg organic fertilizer per ha, F = Jepara variety +1 ton organic fertilizer per ha, G = Kancil variety+1ton organic fertilizer per ha,H = Jepara variety+1500 kg organic fertilizer per ha, I = Jepara variety + 2 ton organic fertilizer per ha. Parameters observed: ability to grow crops, the percentage of plant growth, flowering and harvest, plant height, number of pods, and the percentage of empty pods, plant and wet pods heavy per plot, dried plant and pod weight per plot,there are carried out at harvest, dry seed weight and Aspergillus flavus test. Observations on the plant environment, including: the level of pests and diseases, test N, P, K, organic matter, pH, soil CEC and elements observation. The results indicated that 1) Kancil variety with organic fertilizer 1.5 tons / ha had the highest peanut production because they had adaptif performance ie more resistant to leaf spot and withered base of stem diseases, number of pods 19.80 with weight 25.34 grams and 20.59% empty pods, dry seed weight of 23.14 grams per plant in 100 dry beans weighing 44.54 grams, the weight of dry beans as much as 2.10 tons per ha. 2) All soil treatment before and after the research conducted was containing Aspergillus sp that has a chance of aflatoxin contamination in peanut pods. 3) Economycally at the same fertilization treatment Kancil variety more favorable than Jepara variety and Cidaun strain. The dose of 1.5 tons per hectare fertilizer in Kancil variety gave the highest benefits (Rp. 28. 593 000, -.)compared with other treatments.